1987
DOI: 10.1113/jphysiol.1987.sp016465
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate transport in brush‐border membranes from control and rachitic pig kidney and small intestine.

Abstract: SUMMARY1. Na-Pi co-transport was analysed using renal cortical and small intestinal brush-border membrane vesicles which were isolated from control (normal, heterozygotes) and rachitic piglets (homozygotes).2. A kinetic analysis of Na-dependent initial linear uptake of Pi was performed using vesicles obtained from control animals. The results suggest similar kinetic properties for the renal and small intestinal co-transport system. (i) A sigmoidal dependence on Na concentration of Pi uptake suggests the involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Absorption of P in the small intestine occurs largely via a transcellular pathway that is initiated by transport of P across the brush border membrane. Transport of P through the apical membrane of the intestinal epithelial cell followed by reabsorption across the renal cell brush border membrane is a secondary active transport mechanism which, in non‐ruminants, is dependent upon Na + (Na + /P i co‐transport) 5, 6. A deficiency of Na + may consequently affect the absorption of P. In this study, APD and TPD increased when the NaCl concentration increased from 0.1 to 0.3%, and then decreased, although APD and TPD in the diets with higher levels of NaCl (0.4–0.6%) were still higher than those in the diet with the lowest NaCl level (0.1%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absorption of P in the small intestine occurs largely via a transcellular pathway that is initiated by transport of P across the brush border membrane. Transport of P through the apical membrane of the intestinal epithelial cell followed by reabsorption across the renal cell brush border membrane is a secondary active transport mechanism which, in non‐ruminants, is dependent upon Na + (Na + /P i co‐transport) 5, 6. A deficiency of Na + may consequently affect the absorption of P. In this study, APD and TPD increased when the NaCl concentration increased from 0.1 to 0.3%, and then decreased, although APD and TPD in the diets with higher levels of NaCl (0.4–0.6%) were still higher than those in the diet with the lowest NaCl level (0.1%).…”
Section: Discussionmentioning
confidence: 99%
“…The active transport of P is coupled to cellular Na + uptake by the Na + /P i co‐transporter 5–7. However, only a few studies have been published relating to the effect of NaCl on P i digestibility.…”
Section: Introductionmentioning
confidence: 99%
“…From functional assays, it was shown in the past for several mammalian species, including the pig that P i uptake across the duodenal brush-border membrane is mediated by a secondary, active Na-dependent P i transport system that is stimulated by calcitriol (Quamme, 1985;Brandis et al, 1987;Caverzasio et al, 1987;Schröder et al, 1998b). In a number of laboratory animals as well as human this P i transport system has been identified as the Na + -P i cotransporter NaPi-IIb, a member of the type II Na + -P i cotransporter family SLC34 (Hilfiker et al, 1998;Murer et al, 2004).…”
Section: Phosphate Absorptionmentioning
confidence: 99%
“…Early studies showed that P i transport through the apical membrane of small intestinal epithelial cells is coupled with sodium (4,7,12,21,29,43,47,48). One transporter involved in intestinal P i absorption is the type IIb sodium-coupled P i cotransporter (NaP i -IIb), which has been cloned from rodents and humans (20,25,28,55).…”
mentioning
confidence: 99%